Targeted bidders in government tenders - Matilde Cappelletti; Leonardo M. Giuffrida (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
A set-aside restricts participation in procurement contests to targeted firms. Despite being widely used, its effects on actual competition and contract outcomes are ambiguous. We pool a decade of US federal procurement data to shed light on this empirical question using a two-stage approach. To circumvent the lack of exogenous variation in our data, as a first step we draw on random forest techniques to calculate the likelihood of a tender being set aside. We then estimate the effect of restricted tenders on pre- and postaward outcomes using an inverse probability weighting regression adjustment. Set-asides prompt more firms to bid - that is, the increase in targeted bidders more than offsets the loss of untargeted. During the execution phase, set-aside contracts incur higher cost overruns and delays. The more restrictive the setaside, the stronger these effects. In a subset of our data we leverage an expected spike in set-aside spending and we find no evidence of better performance by winners over a ten-year period.
Keywords: D22; H32; H57; L25; 330; small businesses; set-aside; competition; procurement; public contracts; random forest; firm dynamics